CFD study of the influence of the roughness and partially submerged propeller on its thrust - طالب علي; نوار عباس (Latakia University Journal -Engineering Sciences Series, 2023)
This study aims to determine the influence of the submerged surface roughness of the hull with the propeller of marine vehicles on propulsion at different values ​​of roughness height in several cases, whether on the entire wet surface with the propeller or on the propeller blades only, and the influence of partially submerged propeller on its thrust at different values ​​of the immersion ratio using CFD (Computational Fluid Dynamic). The URANS method and k-ω Shear Stress Transport (SST) model with the ANSYS program were used to solve the Navier-Stokes equations. The Volume of Fluid method was used to capture the free surface and the interaction between the two phases (water and air) around the hull. In addition to using both the frame motion and the mesh motion to calculate the mutual effect between the hull and propeller. The study was carried out on a JBC (Japan Bulk Carrier) model and a DARPA Suboff model. The comparison between the CFD and Exp-results of total resistance and thrust shows a good agreement.